PENGARUH PENGGUNAAN METODE PARTISIPATORI TERHADAP MOTIVASI BELAJAR SISWA SMP NEGERI 3 RAMBAH - Sari, Fitrian (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2016)
The purpose of this research Â was to determine the effect of the use of participatory methods for students motivation SMP N 3 Rambah. This research design that uses a pre-experimental one-group pretest-posttest design. Data collection techniques in this research using the following instruments Questionnaire and tests. Population of this research is all class VII SMP N 3 Rambah totaling 16 students. The sampling technique using saturated sampling is sampling technique when all members of the population as the sample (Sugiyono, 2009). The data analysis technique used is quantitative descriptive and then test Correlation and Simple Linear Regression. Besecl on data analis, Of goals learning tested Based on the calculation of correlation which has been obtained that the value rhitung = 0.992, Anchored by interpretation of the correlation coefficient are in a very strong category, as well as from the regression equation Yâ= 41.28 + 0.89 X. The equation contains koefisien direction that is positive regression evidenced by high learning motivation.